Mircea Eliade and the Function of Reading for Religion in Modernity - Burkhardt, Stefanie (Lecture Series | The Invention of the Modern Religious Bookshelf, 2023)
Mircea Eliade is one of the most influential and widely read historians of religion of the 20th century. Less well known is that he not only published scholarly books on a wide range of topics from yoga to shamanism and comparative analyses of the sacred and profane, but also wrote numerous short stories and novels. These literary texts not only deal with the phenomena and experiences he researched in a complementary way. They are an important part of his work, for they also reflect his conviction that the reading of literature is a way for modern man to access the knowledge and wisdom of homo religiosus. In this sense, the modern religious bookshelf is itself a tool for Eliade to regain access to religious experience and practice in a secularised world. The lecture discusses Eliade's method and theory of Religious Studies as a specific aesthetic of impact (Wirkungsästhetik) and shows how he himself implements it in his literatur